A Description of Transverse Momentum Distributions in p+p Collisions at RHIC and LHC Energies - Jia-Qi Hui; Zhi-Jin Jiang (Advances in High Energy Physics)
It has long been debated whether the hydrodynamics is suitable for the smaller colliding systems such as p+p collisions. In this paper, by assuming the existence of longitudinal collective motion and long-range interactions in the hot and dense matter created in p+p collisions, the relativistic hydrodynamics incorporating with the nonextensive statistics is used to analyze the transverse momentum distributions of the particles. The investigations of the present paper show that the hybrid model can give a good description of the currently available experimental data obtained in p+p collisions at RHIC and LHC energies, except for p and p¯ produced in the range of pT>3.0 GeV/c at s=200 GeV.